Der Klang der Ungleichheit Biografie, Bildung und Zusammenhalt in der vielsprachigen Gesellschaft - Brizić, Katharina (Waxmann, 2022)
Primary school is a unique nucleus of social cohesion. It is here that the diversity of the population is represented together for the last time before they part ways with the transition to secondary school - especially in educational systems as socially unequal as the Austrian and German ones. The first part of the book is devoted entirely to this diversity, based on 160 Viennese mothers and fathers whose children are just about to finish primary school. In multilingual autobiographical narratives, the parents give controversial, powerful insights into their family histories, language biographies, migration or flight and raise their voices against experienced inequality as well as for the future of their children. In the second part, teachers follow with their perceptions and the pressures of "social selection" at the end of the primary school years. The third and final part of the book looks at the result: the success or failure of the children and how it actually came about: How, once again, was glaring social inequality produced, even though no one wanted it to be? Which parental biographies, which competences of the children were successful, thus heard and appreciated by the teachers, and which remained unsuccessful - despite comparable performance? What did the school perceive of the family history, of the diversity of voices in the first place, and what led to the distortions in institutional "listening"? The Sound of Inequality documents the multilingualism and polyphony of our globalised times as well as the responsibilities of the education system by juxtaposing empirical testimonies in a challenging way. The author contrasts the thoroughly serious consequences with interdisciplinary perspectives that strengthen teaching and learning in its function of being the nucleus of a migration society in solidarity.